Meeting Report on Prof. R. Misra Memorial Lecture and Panel Discussion - Pandey, Anvita; Joshi, Harshita; Singh, Ripu Daman; Gumber, Surabhi; Rawat, Gopal S (International Journal of Ecology and Environmental Sciences, 2024)
A meeting report